In vitro characterization of the effects of chronic insulin stimulation in mouse 3T3-L1 and human SGBS adipocytes. (1st January 2020) - Rossi, A.; Eid, M.; Dodgson, J.; Davies, G.; Musial, B.; Wabitsch, M.; Church, C.; Hornigold, D.C.
ABSTRACT: Hyperinsulinemia is the hallmark of the development of insulin resistance and precedes the diagnosis of type 2 diabetes. Here we evaluated the effects of prolonged exposure (≥4 days) to high insulin doses (150 nM) in vitro in two adipose cell types, mouse 3T3-L1 and human SGBS. Chronic insulin treatment significantly decreased lipid droplet size, insulin signalling and insulin-stimulated glucose uptake. 3T3-L1 displayed an increased basal glucose internalization following chronic insulin treatment, which was associated with increased GLUT1 expression. In addition, both cells showed increased basal lipolysis. In conclusion, we report the effects of prolonged hyperinsulinemia in 3T3-L1 and SGBS, highlighting similarities and discrepancies between the cell types, to be considered when using these cells to model insulin-induced insulin resistance.